The Teaching of Speaking in Big Classes - Ruwandi Ruwandi (Register Journal, 2011)
Speaking is the most important language skill. The language user’s capability will be immediately understood and measured through the skill because this is the most visible proficiency. Difficulties of teaching speaking vary dependent upon the class size. Teaching speaking in big classes is more difficult than teaching of it in small classes. The main constraint is the time allotment. To answer the problem, speaking teachers should be creative to set the intensive classroom activities. If this is true, they need to identify students speaking skill to understand their alertness for the following language instructions. Besides that, they are also responsible to identify their basic need in the class whether this is only for question and answer, dialog, discussion, debate, or others. To anticipate the time constraints, the teachers engage to select the possible methods and strategies for presenting the interesting instructional materials. At the end, teachers should divide the time allotment adjust and proportionally for their students so they are able to self-express and share ideas in those interactive classroom situations.keywords; Speaking, Existing Skill;  Need Analysis;  Classroom Management; Methods Strategies ; Presentation